Multivessel percutaneous coronary intervention in patients with stable angina: a common approach? Lessons learned from the EHS PCI registry - Bauer, Timm; Zeymer, Uwe; Hochadel, Matthias; Zahn, Ralf; Gitt, Anselm Kai (Heart and vessels, 2012)
The aim of this study was to evaluate clinical characteristics, procedural details, and outcomes of patients undergoing elective multivessel percutaneous coronary intervention (MV-PCI) in Europe. A total of 7113 patients with stable coronary artery disease and at least two major epicardial vessels with ≥70% stenosis were included in this analysis of the contemporary Euro Heart Survey PCI registry. Patients undergoing MV-PCI (n = 3376, 47.5%) were compared with those with single-vessel PCI (SV-PCI) (n = 3737, 52.5%). Patients with MV-PCI were more likely to have congestive heart failure, whereas those with SV-PCI more often suffered from noncardiac comorbidities. Hospital mortality (0.1% vs 0.3%) and the incidence of nonfatal postprocedural myocardial infarction (1.0% vs 0.7%) were low in patients with MV-PCI and SV-PCI. In the multivariate analysis, no significant difference in the incidence of hospital death (odds ratio (OR) 0.44, 95% confidence interval (CI) 0.15-1.27) could be observed between the two groups. However, the risk for postprocedural myocardial infarction (OR 1.57, 95% CI 0.93-2.67) tended to be higher among patients undergoing MV-PCI. Independent determinants for performing MV-PCI were age, comorbidities, and coronary anatomy. In Europe almost half of all patients with multivessel disease were treated with MV-PCI. Hospital complications were low, but a trend toward a higher rate of postprocedural myocardial infarctions was seen in patients with MV-PCI.
First online: 09 November 2011
Gesehen am 09.11.2018